The Impact of Religious and National Belonging on Attitudes Concerning the Social Importance of Religion - Ziebertz, Hans-Georg (Journal of empirical theology, 2017)
Culture and religion are both collective phenomena. Social identity theory shows how both can function as a connective frame of reference for a certain group of human beings. Frames are unique; nevertheless, different frames can overlap each other. In this research, both big categories will be used to explore if and how they predict attitudes towards the social importance of religious institutions. Religious institutions are guided by religious authorities and these authorities have a specific responsibility to keep these institutions alive and prepare them for the future. In this research, respondents were asked how religious institutions can best be prepared for the future: whether they should use their social authority, moral authority, spiritual or cultural authority? The second and main question of this paper is: can the appreciated social importance of religious institutions be predicted by religious or non-religious reasons, i.e. by either respondents’ religious belonging or their national identity? A requirement for such research is the availability of a cross-cultural and cross-religious sample. In this paper, data were taken from the “Religion and Human Rights” programme and respondents from 14 countries (N=13.004) were included in the analysis. The findings show that respondents regard the social importance of religion differently and that differences depend on respondents’ country of citizenship and their religious belonging. If the weight of these influences is compared, respondents’ views are more strongly predicted by their national than by their religious belonging. The findings also show that there is an overlap between national culture and religion, which explains a certain percentage of the variance.